Indian Journal of Pure and Applied Mathematics - Misra, Gadadhar; SpringerLink (Online service) (New Delhi : Indian National Science Academy : Imprint: Indian National Science Academy, co-published with Springer.)
For a paper to be considered for publication, it is a precondition that it is not submitted for publication elsewhere and contains results that are new, significant and of interest to wide sections of the mathematical community. Editors may invite papers on special topics of current interest. All papers, whether contributed or invited, will be refereed.
Keywords: Mathematics; Applied mathematics; Engineering mathematics; Numerical analysis; Mathematics, general; Applications of Mathematics; Numerical Analysis